Efeito de um mês de destreinamento sobre a aptidão física relacionada à saúde em programa de mudança de estilo de vida - Michelin, Edilaine [UNESP]; Coelho, Christianne de Faria [UNESP]; Burini, Roberto Carlos [UNESP] (FapUNIFESP (SciELO), 2008)
Physical exercise induces hemodynamic/ventilatory and neuromuscular adaptations that can be reverted with interruption of the training program. The aim of the present study was to evaluate the effect of detraining on physical fitness related to health. Forty-four healthy subjects, both male and female, aged 57.6±8.9 years performed the 'Mexa-se Pró-Saúde' protocol with nutritional orientation and supervised physical exercises for nine months. The program consisted of aerobic, localized muscular endurance and flexibility exercises, with duration 80 minutes/session, five days/week. Only subjects who participated in the program for more than three days/week have been selected. The detraining period was one month. Weight (kg) and height (m) were measured and the body mass index (BMI) calculated. Additionally, motors tests to evaluate the flexibility (FLEX), strength of lower limbs (SLL) and upper limbs (SUL), and maximal oxygen uptake (VO2máx) were conducted in the beginning of the study (MI), after nine months of practicing (MT) and after detraining period (MD). ANOVA (p<0.05) and Tukey test to show the difference between groups when it evidence were used for statistical treatment. The results showed that the gains of 22% and 7% on SLL and VO2máx respectively, obtained with the training, have not changed during the detraining period; however, the flexibility gain of 8% returned back to baseline after the detraining period. BMI and SUL did not change during the study. Although the lower limbs strength gains and maximal oxygen uptake obtained have been kept, one month of detraining was enough for losing the flexibility acquired.
Effects of one month detraining over health-related physical fitness in a lifestyle change program
Keywords: Health; Physical exercise; Training interruption